The Whole Is More than Its Parts: A Multidimensional Construct of Values in Consumer Information Search Behavior on SNS - Ofrit Kol; Shalom Levy (Journal of Theoretical and Applied Electronic Commerce Research, 2022)
The notion of consumer values has been a key factor in understanding consumer behavior and has attracted the attention of various scholars in e-commerce. The aims of this study are to conceptualize a multidimensional construct of consumer information value (CIV) on social network sites (SNS), to examine the construct empirically, and to investigate the nature of its relationships with consumer information search behavior, i.e., the use of information channels on SNS. Quantitative research was conducted using a representative sample of 612 Facebook users. The use of a higher-order construct and structural equation modeling procedures reveals that the following five value constructs—Economic, Psychological, Social, Functional and Hedonic values—are significant facets of the CIV. It suggests that the CIV model is a powerful tool that directly explains consumer information search behavior and has better explanatory power than the sum of its parts.